Network Aspect of Multilateral Diplomacy - I. A. Kunina (Научный диалог)
The relevance of the study is due to the process of structural reorganization of the entire global system of international relations. It is noted that, along with military power, the economic, scientific, technical, and information spheres of state’s activities are coming to the fore, stimulating their work in the international arena. It is emphasized that this circumstance determines the complex interdependence of the main actors of international relations at the present stage. It is argued that the changes taking place in the world require a revision of the bloc approach to solving international problems and the search for new formats of cooperation that would help build constructive international cooperation. It is pointed out that multilateral diplomacy is called upon to play a significant role in modern international relations; moreover, it is becoming the main means of collective management of global world processes. It is clarified that “network diplomacy” is becoming the format of multi-vector diplomacy, based on flexible types of participation in multilateral structures. The author makes a comprehensive analysis of the phenomenon of network diplomacy. Particular attention is paid to the study of the mechanisms for the implementation of this type of diplomacy, and their application in practice. The issue of the diversity of participants in this process is considered, taking into account the formats of interaction between them within the framework of network diplomacy.